Accurate two-stage frequency offset estimation for coherent optical systems - Huang, Dezhao (2013)
We present a two-stage feedforward frequency offset estimation (FOE) algorithm on the basis of the phase-difference method. The first stage of the proposed FOE generates a rough FOE through averaging the phase difference between two adjacent symbols and compensates the signals. The second stage of the FOE estimates the residual FO through averaging the phase difference of two symbols with distance L , which provides a significantly larger noise-tolerance and thus improves system performance. The proposed FOE can be applied to both quadrature phase-shift keying and 16-quadrature amplitude modulation systems. Simulations show that the mean square error of the proposed FOE can be reduced through an order of two in magnitude under small laser linewidth situation compared with the classic phase-difference-based FOE. The experimental result shows that the proposed FOE gives 0.6-dB optical-signal-to-noise-ratio improvement against the classic FOE, which validates its usefulness.